PL.31 A Simple Classification System for Maternal Traumatic Injuries Associated with Second Stage Caesarean Section. (26th April 2013) - Angala, P; Raja, M; Ikomi, M; Varma, R
Abstract : Background: Caesarean section at full dilatation can be a technically demanding procedure and has a consistent association with laceration injuries to uterus, cervix and vagina. Recent Scottish Morbidity data showed 25% of women delivered by emergency caesarean section and experiencing massive obstetric haemorrhage (MOH) were delivered in the 2 nd stage of labour. 16.3% of all the MOH cases were caused by extensions of the uterine incisions and/or broad ligament haematomas. It is therefore surprising that to date a universally accepted formal classification system for maternal injuries (similar to that of obstetric anal sphincter injuries) relating to this scenario, is yet to emerge. Aim: To design a simple classification system and to apply this in a review of second stage deliveries at a UK University hospital Method: A retrospective analysis of the labour and operation notes of 60 patients delivered by caesarean section at full dilatation during a 9 month period in 2010. Uterine extensions were graded as: Grade 1 [easy to suture, no increase in operating time], Grade 2 [increased operating time and total blood loss] or Grade 3 [involvement of uterine artery, cervix, vagina, or bladder]. Results: 25% [15/60] had uterine extensions of which 53% were Grade1, 27% were grade 2 and 20% were grade 3. It was easy to grade the extensions retrospectively. Grade 3 extensions resulted in longer operating times and higher blood transfusion rates. Conclusion: A simple classification of uterine extensions can improve the consistency of contemporaneous documentation and has potential as a research tool.